2021
DOI: 10.1016/j.canep.2020.101857
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of radiation induced sarcoma attributable to radiotherapy in adults: A retrospective cohort study in the SEER cancer registries across 17 primary tumor sites

Abstract: Background: Previous studies have noted the incidence of radiation-induced sarcomas (RIS) but have not investigated the relative risk (RR) of developing RIS based on primary tumor organ disease site. By examining data from the Surveillance, Epidemiology, and End Results (SEER) database, we hypothesized that breast cancer would have a higher incidence of RIS compared to seventeen other primary cancer sites. Methods: This was a retrospective cohort study that examined pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 62 publications
(60 reference statements)
1
20
0
1
Order By: Relevance
“…RIAS is a rare type of secondary angiosarcoma. Recent data from SEER summarized by Snow et al [ 7 ] showed that breast cancer patients had the highest incidence of secondary sarcomas (0.03–0.2%). According to the same authors, considering all post-radiation sarcomas, breast cancer patients have the highest RIS number and account for 52.1% of all radiation-induced sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…RIAS is a rare type of secondary angiosarcoma. Recent data from SEER summarized by Snow et al [ 7 ] showed that breast cancer patients had the highest incidence of secondary sarcomas (0.03–0.2%). According to the same authors, considering all post-radiation sarcomas, breast cancer patients have the highest RIS number and account for 52.1% of all radiation-induced sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative incidence of developing RIS in patients who received radiotherapy was 0.32% at 15 years, compared to 0.23% in patients who did not receive radiotherapy [15]. In a more recent analysis of the SEER database, Snow et al found the incidence of RIS of the breast to be 0.02% at a median follow-up of 9.6 years [11]. A major limitation of SEER data is that it does not report data on radiation treatment or systemic treatment received [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent analysis of the SEER database, Snow et al found the incidence of RIS of the breast to be 0.02% at a median follow-up of 9.6 years [11]. A major limitation of SEER data is that it does not report data on radiation treatment or systemic treatment received [11,15]. The SEER data analysis also excluded patients for whom data were missing, therefore likely underestimating the true incidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations